**Construct the switching network of the given compound statements. Then, construct another switching network of the equivalent statement by applying the laws of logic: 1. p v (~p v q) v (p v ~q) ] ^ ~q 2. (p → q) ^ (p ↔ q)**

The **Answer to the Question**

is below this banner.

**Here's the Solution to this Question**

$P+[(\tilde p+q)+(p+\tilde q)]*\tilde q \\ P+(1+1)* \tilde q\\ P+1*\tilde q\\ P+\tilde q\\\\ 2)( (p\implies q))\land (p \leftrightarrow q)\\ (\tilde p \bigvee q)\bigwedge (\tilde p\tilde q+qp)\\ \tilde p\tilde q+pq\\ \\$